2020
DOI: 10.1017/s1368980020001664
|View full text |Cite
|
Sign up to set email alerts
|

Social, economic and cultural influences on adolescent nutrition and physical activity in Jimma, Ethiopia: perspectives from adolescents and their caregivers

Abstract: Objective: To explore influences on adolescent diet and physical activity, from the perspectives of adolescents and their caregivers, in Jimma, Ethiopia. Design: Qualitative design, using focus group discussions (FGD). Setting: A low-income setting in Jimma, Ethiopia. Participants: Five FGD with adolescents aged 10–12 years and 15–17 years (n 41) and three FGD with parents (n 22) were conducted. Results: Adolescents displayed a holist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Our finding is supported by similar study conducted in Ethiopia [ 38 ]. In Ethiopia culturally boys had more free time to participate in outdoor activities compared to adolescent girls; adolescent boys physical activity may influence their body weight [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is supported by similar study conducted in Ethiopia [ 38 ]. In Ethiopia culturally boys had more free time to participate in outdoor activities compared to adolescent girls; adolescent boys physical activity may influence their body weight [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are more limited opportunities for physical activity in urban environments, especially for girls, because of overcrowding and lack of space. In a recent qualitative study, we identified that boys have more opportunity for leisure time and outdoor physical activity than girls [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies (67.7%) used focus groups (53, 55-60, 62, 64-66, 68-73, 75-77, 81, 83, 84), with 30.4% of these conducting mixed-gender groups (55,56,58,60,70,71,77). Parents were included in 26.1% of studies (53,65,66,72,73,76,81), but only present with adolescents during data collection in one study (53). Semi-structured interviews (26.5%) (25, 54, .…”
Section: Study Methodsmentioning
confidence: 99%
“…Australia (62, 63), Costa Rica (64, 65), Bangladesh (66,67), Ireland (68, 69), and Sweden (70, 71) all had two studies (5.9%) each. Ethiopia (72), India (73), Indonesia (74), Iran (75), Morocco (76), Netherlands (77), Peru (78), Scotland (79), Slovakia (80), South Africa (81), United Arab Emirates (82), and United Kingdom (83) all had one study (2.9%) each. One study considered data from Canada and India, these countries were evaluated separately (84).…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation